Thermal energy storage – overview and specific insight into nitrate salts for sensible and latent heat storage - Pfleger, Nicole; Bauer, Thomas; Martin, Claudia; Eck, Markus; Wörner, Antje (Beilstein Journal of Nanotechnology, 2015)
Thermal energy storage (TES) is capable to reduce the demand of conventional energy sources for two reasons: First, they prevent the mismatch between the energy supply and the power demand when generating electricity from renewable energy sources. Second, utilization of waste heat in industrial processes by thermal energy storage reduces the final energy consumption. This review focuses mainly on material aspects of alkali nitrate salts. They include thermal properties, thermal decomposition processes as well as a new method to develop optimized salt systems.
Keywords: eutectic mixture; molten salt; nitrate; phase change material; thermal decomposition